2017
DOI: 10.1371/journal.pone.0185988
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of tense and relaxed state polymerized human hemoglobin regulate oxygen affinity and tissue construct oxygenation

Abstract: Pure tense (T) and relaxed (R) quaternary state polymerized human hemoglobins (PolyhHbs) were synthesized and their biophysical properties characterized, along with mixtures of T- and R-state PolyhHbs. It was observed that the oxygen affinity of PolyhHb mixtures varied linearly with T-state mole fraction. Computational analysis of PolyhHb facilitated oxygenation of a single fiber in a hepatic hollow fiber (HF) bioreactor was performed to evaluate the oxygenation potential of T- and R-state PolyhHb mixtures. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 46 publications
8
36
0
Order By: Relevance
“…PolyhHbs were synthesized from human Hb and glutaraldehyde using our previously reported procedure [ 40 ]. Expired human plasma for viscosity analysis was generously donated by Transfusion Services, Wexner Medical Center, The Ohio State University, Columbus, Ohio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PolyhHbs were synthesized from human Hb and glutaraldehyde using our previously reported procedure [ 40 ]. Expired human plasma for viscosity analysis was generously donated by Transfusion Services, Wexner Medical Center, The Ohio State University, Columbus, Ohio.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently explored the biophysical properties of both high and low O 2 affinity HBOCs via the production of polymerized Hbs locked in either the relaxed (R) or tense (T) quaternary state [ 36 38 ]. We have used information from prior studies and a recent down selection study to better engineer polymerized Hbs with decreased in vivo oxidation and increased circulatory half-life [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated that polymerized human Hb (PolyhHb) frozen in the tense quaternary state (T-state) can regulate O 2 transport to cells housed in the ECS. 17 This can prevent the development of hypoxia and hyperoxia, allowing the hepatocytes to function more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Weekly treatment with low MW PolyHb at low doses insufficient to increase blood O 2 carrying capacity with short circulatory half-life (10 hours intravascular half-life) limits the oxygenation potential of PolyHb as a cisplatin sensitizing mechanism in NSCLC. In our previous study, we dosed every two days with higher concentrations of large MW PolyHb (24 hours intravascular half-life) to significantly increase oxygenation in breast tumors and directly induce O 2 dependent antitumor activity [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…R-state PolyHb was prepared from human Hb (hHb) extracted from human RBCs as described previously [ 48 ]. After purifying the material, we measured the biophysical properties of the PolyHb [ 31 ]. The cyanomethemoglobin method was used to measure the Hb concentration and the methemoglobin (metHb) level of hHb/PolyHb solutions [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%